Reproductive pathways in Hieracium s.s. (Asteraceae): strict sexuality in diploids and apomixis in polyploids - Mráz, Patrik; Zdvorák, Pavel (Annals of botany, 2019)
Background and Aims: Apomixis or asexual seed reproduction is a key evolutionary mechanism in certain angiosperms providing them with reproductive assurance and isolation. Nevertheless, the frequency of apomixis is largely unknown, especially in groups with autonomous apomixis such as the diploid-polyploid genus Hieracium. Methods: Using flow cytometric analyses, we determined the ploidy level and reproductive pathways (sexual vs. apomictic) for 7616 seeds originating from 946 plants belonging to >50 taxa sampled at 130 sites across Europe. Key Results: Diploid seeds produced by diploids were formed exclusively by the sexual pathway after double fertilization of reduced embryo sacs. An absolute majority of tri- and tetraploid seeds (99.6 %) produced by tri- and tetrapolyploid taxa were formed by autonomous apomixis. Only 20 polyploid seeds (0.4 %) were formed sexually. These seeds, which originated on seven polyploid accessions of four taxa, were formed after fertilization of either unreduced embryo sacs through a so-called triploid bridge or reduced embryo sacs, and frequently resulted in progeny with an increased ploidy. In addition, the formation of seedlings with increased ploidy (4x and 6x) was found in two triploid plants. This is the first firm evidence on functional facultative apomixis in polyploid members of Hieracium sensu stricto (s.s.). Conclusions: The mode of reproduction in Hieracium s.s. is tightly associated with ploidy. While diploids produce seeds exclusively sexually, polyploids produce seeds by obligate or almost obligate apomixis. Strict apomixis can increase the reproductive assurance and this in turn can increase the colonization ability of apomicts. Nevertheless, our data clearly show that certain polyploid plants are still able to reproduce sexually and contribute to the formation of new cytotypes and genotypes. The finding of functional facultative apomicts is essential for future studies focused on evolution, inheritance and ecological significance of apomixis in this genus.
Keywords: fertilizace; apomixie; Asteraceae; Apomixis; Fertilization; polyploidie; Diploidy; Polyploidy; diploidie